Transynaptic Action of Botulinum Neurotoxin Type A at Central Cholinergic Boutons - Caleo, Matteo (J Neurosci, 2018)
Botulinum neurotoxin Type A (BoNT/A) is an effective treatment for several movement disorders, including spasticity and dystonia. BoNT/A acts by cleaving synaptosomal-associated protein of 25 kDa (SNAP-25) at the neuromuscular junction, thus blocking synaptic transmission and weakening overactive muscles. However, not all the therapeutic benefits of the neurotoxin are explained by peripheral neuroparalysis, suggesting an action of BoNT/A on central circuits. Currently, the specific targets of BoNT/A central activity remain unclear. Here, we show that catalytically active BoNT/A is transported to the facial nucleus (FN) after injection into the nasolabial musculature of rats and mice. BoNT/A-mediated cleavage of SNAP-25 in the FN is prevented by intracerebroventricular delivery of antitoxin antibodies, demonstrating that BoNT/A physically leaves the motoneurons to enter second-order neurons. Analysis of intoxicated terminals within the FN shows that BoNT/A is transcytosed preferentially into cholinergic synapses. The cholinergic boutons containing cleaved SNAP-25 are associated with a larger size, suggesting impaired neuroexocytosis. Together, the present findings indicate a previously unrecognized source of reduced motoneuron drive after BoNT/A via blockade of central, excitatory cholinergic inputs. These data highlight the ability of BoNT/A to selectively target and modulate specific central circuits, with consequent impact on its therapeutic effectiveness in movement disorders. SIGNIFICANCE STATEMENT Botulinum neurotoxins are among the most potent toxins known. Despite this, their specific and reversible action prompted their use in clinical practice to treat several neuromuscular pathologies (dystonia, spasticity, muscle spasms) characterized by hyperexcitability of peripheral nerve terminals or even in nonpathological applications (i.e., cosmetic use). Substantial experimental and clinical evidence indicates that not all botulinum neurotoxin Type A (BoNT/A) effects can be explained solely by the local action (i.e., silencing of the neuromuscular junction). In particular, there are cases in which the clinical benefit exceeds the duration of peripheral neurotransmission blockade. In this study, we demonstrate that BoNT/A is transported to facial motoneurons, released, and internalized preferentially into cholinergic terminals impinging onto the motoneurons. Our data demonstrate a direct central action of BoNT/A.